The decreased in vitro chemotactic activity of polymorphonuclear leukocytes of newborns and infants - Miler, I; Vondrácek, J; Hromádková, L (Folia microbiologica, 1979)
Using Boyden's technique, a statistically significant decrease in the chemotactic activity of polymorphonuclear (PMN) leukocytes was found during the early postnatal period, i.e. in the cord blood and in blood of newborns within the first 10-15 d of life after stimulation of cells with both zymosan-activated adult serum (ZAS) and with an abacterial filtrate of Escherichia coli broth culture (ECF). After this period, the responsiveness of leukocytes to both chemotactic agents increased and remained at the same level during the whole observation period, i.e. up to the age of 6 months. Nevertheless even then it did not reach fully the responsiveness of the leukocytes of mothers and pregnant women. Zymosan-activated serum was shown to be a more potent chemotactic stimulus to leukocytes of infants as compared to the E. coli filtrate.
Keywords: Infant, Newborn; Chemotaxis, Leukocyte; Escherichia coli; novorozenec; Infant; dospělí; Humans; Fetal Blood; chemotaxe leukocytů; Adult; Neutrophils; fetální krev; neutrofily; kojenec; Zymosan; lidé; zymosan